Host-Region : Safe Folklore and the Negotiation of Difference In Post-Socialist Diasporas in Newfoundland - Lesiv, Mariya (Anthropologica, 2021)
Many studies of diasporas focus on (large) locales where sizable diasporic populations provide room for group formation based on a single ethnicity. Scholars often treat such regions as representative of larger units, defining hostland in broad geopolitical categories of countries and even continents. Based on ethnographic research devoted to immigrants from post-Socialist Europe and Asia to the Canadian island of Newfoundland, I propose the concept of host-region to emphasize a regional perspective in diaspora studies. The overall small newcomer population and the unique socio-cultural context of the island result in regionally-specific diasporic group-building dynamics, stimulating new Newfoundlanders to expand the notion of their people beyond likeminded co-ethnics. Safe home-region folklore, namely, select cultural expressions that reinforce a sense of unity and do not cause tensions within a group, offers points of connection. However, contrary to many studies that emphasize the notion of commonality within groups, I show that difference, reinforced by continuous turbulence in the home-region, can be equally important in group-building endeavors. De nombreuses études sur les diasporas se concentrent sur les (grandes) régions où d’importantes populations diasporiques permettent la formation de groupes fondés sur une seule ethnicité. Les chercheurs traitent souvent ces régions comme représentatives d’unités plus vastes, définissant les terres d’accueil dans de larges catégories géopolitiques de pays et même de continents. À partir d’une recherche ethnographique consacrée aux immigrants de l’Europe et de l’Asie post-socialistes sur l’île canadienne de Terre-Neuve, je propose le concept de région d’accueil pour mettre en évidence une perspective régionale dans les études sur les diasporas. La faible population globale des nouveaux arrivants et le contexte socio-culturel unique de l’île entraînent une dynamique de constitution de groupes diasporiques spécifiques à la région, ce qui incite les nouveaux ...